Thermoregulation and its disorders in the children’s perioperative period - Dobrowoska-Czopor, Barbara; Maj, Agnieszka Paula; Czykieta, Izabela (Journal of Education, Health and Sport, 2019)
Disorders of termoregulation is a phenomeon that can occur as a result of any kind of anaesthesia. In the perioperative period, infants and small children are most exposed to significant and dangerous changes in body temperature, especially hypothermia. When the body cools to values under 36˚C during simple surgery, it is called uncontrolled hypothermia and can be dangerous to the health or even lifethreating to a small patient. Preventive measures of intraoperative accidential hypothermia are according room temperature. Hypothermia as an intended phenomenon artificially produced is used in such medical fields as:• cardiosurgery in cases of cardiotomy surgery in infants• neurosurgery in lowering intracranial pressure• analgesia through cooling as an effective pain - relieving methodDisorders of termoregulation mechanism leading to rising body temperature is called hyperthermia. It can occur as a sudden reaction to an anaesthetic agent (halothane, enufluran, izofluran, sewofluran, desfluran, suksametonium) revealed during anaesthesia – a genetically determined disease called Fulminant Hyperthermia. The essence of hyperthermia treatment is early diagnosis and fast treatment relying on the removal of causes and symptoms and, above all, needs to be preventative.Regular measurement of both surface and central temperature can allow for quick action against hypothermia or hyperthermia in children.